Champions are racers, not pacers: an analysis of qualification patterns of Olympic and IAAF World Championship middle distance runners. Issue 22 (17th November 2018) - Hanley, Brian; Hettinga, Florentina J.
ABSTRACT: The aim of this study was to analyse qualification patterns in middle distance running and identify whether athletes adopt theoretically optimal tactics, or whether the will to win overrides these. The performances of 295 men and 258 women finalists in the Olympic and IAAF World Championship 800 m and 1500 m events from 1999 to 2017 were analysed across all three rounds of competition. Finishing position, time and ranking amongst all competitors were found for each athlete. Position in the final was correlated with finishing position in the heats and semi-finals (all P < 0.001), but not with finishing times in those rounds. Of the 57 champions, 40 won both their heat and semi-final, even though a lower automatic qualification position would have been sufficient, and only 18 achieved a season's best time in the final. The will to win amongst the eventual champions (and other medallists) suggests predominantly ego oriented behaviour that is encouraged by a performance climate, and which did not appear to differ between men and women. Coaches and athletes are recommended to note that championship-specific physiological and psychological factors are important to develop in training and prior competition to improve both short- and long-term championship strategies.